(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: According to the World Health Organization, non-adherence to treatment or poor adherence is considered an important reason leading to poor blood pressure control, leading to serious complications and death in hypertensive patients. Objectives: Analysis some related factors and barriers to treatment adherence of hypertensive patients at University Hospital of Medical & Pharmacy, Vietnam National University, 2023. Methods: Cross-sectional survey. Quantitative combined with qualitative. Results: Researched the experience of 320 hypertensive patients showed that, the rate of patient compliance was high (10%), medium (53.7%), and low (36.3%). Relevant factors includes: Education level, duration of illness, family history, distance from home to hospital, waiting time for examination, satisfaction, concern for relatives, and knowledge of disease. Four groups of barrier factors includes: Patient characteristics, quality of medical examination and treatment services, side effects of drugs and lack of family support. Conclusion: Patients’ compliance with hypertension treatment is still limited. Groups of related factors and barriers affecting patient compliance with treatment include patient characteristics (lack of knowledge about the disease), quality of medical examination and treatment services (long waiting times, unsatisfactory dissatisfaction with the medical staff’s explanation), medication side effects, and lack of family support.